BGer 4A 210/2010 vom 1. Oktober 2010 - Bundesgericht (2010)
acte illicite; prescription; dommage [4A_210/2010] acte illicite; prescription; dommage [4A_214/2010] acte illicite; prescription; dommage [4A_216/2010] | Droit des obligations (en général)